2012
DOI: 10.1016/j.yexcr.2012.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Human midbrain precursors activate the expected developmental genetic program and differentiate long-term to functional A9 dopamine neurons in vitro. Enhancement by Bcl-XL

Abstract: Understanding the molecular programs of the generation of human dopaminergic neurons (DAn) from their ventral mesencephalic (VM) precursors is of key importance for basic studies, progress in cell therapy, drug screening and pharmacology in the context of Parkinson's disease. The nature of human DAn precursors in vitro is poorly understood, their properties unstable, and their availability highly limited. Here we present positive evidence that human VM precursors retaining their genuine properties and long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 77 publications
(172 reference statements)
6
21
0
Order By: Relevance
“…The percentage of total cells expressing markers characteristic of differentiated VM hNSCs, like β-III-tubulin, GFAP and TH, was compared among samples ( Figure 4B, C). No significant differences between control and MNPs-labeled cells were observed, demonstrating that MNPs do not affect the ability of hVM cells to differentiate into glial cells, neurons and, specifically, dopaminergic neurons, obtaining similar results for THand β-III-tubulin-positive cells (17% and 25% respectively) to those previously described in [7]. Thus, these results demonstrate that labeling VM hNSCs cells with optimal doses of MNPs does not affect their stemness and differentiation potential.…”
Section: Effects Of Mnps On Cell Stemness and Differentiationsupporting
confidence: 84%
See 1 more Smart Citation
“…The percentage of total cells expressing markers characteristic of differentiated VM hNSCs, like β-III-tubulin, GFAP and TH, was compared among samples ( Figure 4B, C). No significant differences between control and MNPs-labeled cells were observed, demonstrating that MNPs do not affect the ability of hVM cells to differentiate into glial cells, neurons and, specifically, dopaminergic neurons, obtaining similar results for THand β-III-tubulin-positive cells (17% and 25% respectively) to those previously described in [7]. Thus, these results demonstrate that labeling VM hNSCs cells with optimal doses of MNPs does not affect their stemness and differentiation potential.…”
Section: Effects Of Mnps On Cell Stemness and Differentiationsupporting
confidence: 84%
“…Recent pre-clinical research has demonstrated that immortalized human NSCs, derived from VM (hVM1 cell line) and modified for the elevated expression of Bcl-XL (hVM1-highBcl-XL cells), have the potential to differentiate into DAn in vivo at a high rate [5][6][7][8][9]. After transplantation in hemiparkinsonian rats, these hVM cells survive, integrate, and differentiate into DAn, alleviating behavioral motor asymmetry and skilled paw use [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all cells expressed this general marker of neural precursor cells, which was in accordance with previous studies showing that both the midbrain stem cell line and the forebrain stem cell line express nestin even after long-term in vitro propagation [34], [35], [37], [38], [47]. We also found GFAP expression during propagation but mainly in forebrain-derived cultures.…”
Section: Discussionsupporting
confidence: 92%
“…This could reflect differences in neuronal and glial differentiation capacity or region-specific requirements of the NSCs. In favour of this hypothesis is the fact that we developed our dopaminergic differentiation protocol using the midbrain-derived cell line [18] and with the aim of generating authentic and functional dopaminergic neurons with A9 (substantia nigra) characteristics [39], [47]. Thus, the applied protocol may not be optimal, when it comes to guiding NSCs from other brain regions towards the A9 dopaminergic phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation